2016
DOI: 10.1016/j.jallcom.2015.11.185
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the accumulation of ion-beam damage in Ni and NiFe explained by atomistic simulations

Abstract: Following low-dose irradiation with a 3 MeV beam of Au ions, i.e. less than one displacement per atom, a lower number of defects were experimentally observed in NiFe than in pure Ni. At higher doses, more damage is observed in NiFe than in pure Ni. Also, at these high doses, defect structures are observed deep in the material, far from the region where ions are implanted, more so in Ni than in NiFe. In this study, these experimental results are explained using atomistic modeling. Sequences of overlapping displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…If this is the case, one might be able to tune alloy composition to enhance such primary damage reduction at the high end of the PKA spectrum. Likewise, the kinetic evolution of the microstructure created by the cascade on longer timescales has an important effect on defect cluster size [5]. These issues certainly warrants further investigation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…If this is the case, one might be able to tune alloy composition to enhance such primary damage reduction at the high end of the PKA spectrum. Likewise, the kinetic evolution of the microstructure created by the cascade on longer timescales has an important effect on defect cluster size [5]. These issues certainly warrants further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…These alloys possess a simple face centered cubic structure (fcc), but are made of several principle elements (such as NiFeCoCrMn), in contrast with conventional alloys that typically contain only one principle component. This high chemical complexity was shown to reduce electronic [2,3] and phonon [4] mean free paths, as well as slow down defect mobility [5,6]. While these properties are known to be important for radiation damage evolution, the mechanisms that explain energy dissipation and defect production in these systems remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 8b 1 , the yellow area in the twodimensional contour map is considered as the effective absorption area. The composite of Co@pNGC-600 can achieve an effective absorption at 3.0-17.8 GHz by adjusting the coating thickness in the range of 2.0-5.5 mm.…”
Section: Resultsmentioning
confidence: 99%
“…In everyday life, radiation will not only interfere with the normal operation of the electronic equipment but also produce a great threat to the ecological environment and human health. 1,2 Furthermore, in the military environment, the radar detection technology causes a serious threat to the abilities of survivability and penetration of military targets. The application of EM absorption materials is a wise and effective method to avoid the acquisition of radar and achieve a stealth mode.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the molecular dynamics (MD) simulations [32,38,39] also show that the mobility of defects is lower in multi-component solid solution than in pure metals, and the formation of large extended defects is suppressed in multi-component disordered solid solution alloys. Jin et al [40] has also shown that the volume swelling is reduced with increasing the number elements in disordered solid solution, which hints that the volume swelling is closely related to the entropy of mixing of the solid solution.…”
Section: Discussionmentioning
confidence: 99%